Antibody screening identifies 78 putative host proteins involved in Cyprinid herpesvirus 3 infection or propagation in common carp, Cyprinus carpio L. Issue 8 (24th January 2013) - Gotesman, M; Soliman, H; El‐Matbouli, M
Abstract Cyprinid herpesvirus 3 (CyHV‐3) is the aetiological agent of a serious and notifiable disease afflicting common and koi carp, Cyprinus carpio L., termed koi herpesvirus disease (KHVD). Significant progress has been achieved in the last 15 years, since the initial reports surfaced from Germany, USA and Israel of the CyHV‐3 virus, in terms of pathology and detection. However, relatively few studies have been carried out in understanding viral replication and propagation. Antibody‐based affinity has been used for detection of CyHV‐3 in enzyme‐linked immunosorbent assay and PCR‐based techniques, and immunohistological assays have been used to describe a CyHV‐3 membrane protein, termed ORF81. In this study, monoclonal antibodies linked to N‐hydroxysuccinimide (NHS)‐activated spin columns were used to purify CyHV‐3 and host proteins from tissue samples originating in either CyHV‐3 symptomatic or asymptomatic fish. The samples were next analysed either by polyacrylamide gel electrophoresis (PAGE) and subsequently by electrospray ionization coupled to mass spectrometry (ESI‐MS) or by ESI‐MS analysis directly after purification. A total of 78 host proteins and five CyHV‐3 proteins were identified in the two analyses. These data can be used to develop novel control methods for CyHV‐3, based on pathways or proteins identified in this study.